Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pembelajaran Bahasa Arab - Misbahus Surur (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2020)
This study aims to explain the extent to which the use of information and communication technology is part of the language learning model design. This research is designed to find an ICT-based Arabic learning model. This research assumes that there is an integration of various fields of study with information and communication technology, including learning Arabic, which is very important to be developed, especially in this digital era. However, the obstacles experienced by several educational institutions, especially educators, do not yet have and find a clear format in using information and communication technology in an effort to integrate the two scientific fields. This study uses research and development with qualitative research methods. This research was conducted in three stages: introduction, development and implementation. The research sample used was purposive sampling. Data collection techniques were carried out by observation, interviews and documentation studies. The results showed that the use of ICT (Information and Communication Technology) which is the design of the Arabic language learning model developed in MTs. Nyai H. Ashfiyah Surabaya is a model of "al-hasub al-ittishalî", namely a computer-based communicative Arabic learning model. In this model, materials and other learning tools are designed in a computer program. Through this model, the teacher functions as a learning motivator for students and a mediator on materials that require explanation among students